2005
DOI: 10.1126/science.1110064
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Rotor of the V-Type Na + -ATPase from Enterococcus hirae

Abstract: The membrane rotor ring from the vacuolar-type (V-type) sodium ion-pumping adenosine triphosphatase (Na+-ATPase) from Enterococcus hirae consists of 10 NtpK subunits, which are homologs of the 16-kilodalton and 8-kilodalton proteolipids found in other V-ATPases and in F1Fo- or F-ATPases, respectively. Each NtpK subunit has four transmembrane alpha helices, with a sodium ion bound between helices 2 and 4 at a site buried deeply in the membrane that includes the essential residue glutamate-139. This site is prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
359
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(376 citation statements)
references
References 28 publications
15
359
1
1
Order By: Relevance
“…We think that PomA-N194 might be one of the most important residues for ion specificity, although there are probably other residues that contribute. NtpK, which is a V-ATPase rotor ring component, coordinates Na + with the essential carboxyl group of E139, the carbonyl group of Q65 and Q110, the hydroxyl group of T64 and the main chain carbonyl group of L61 (Murata et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We think that PomA-N194 might be one of the most important residues for ion specificity, although there are probably other residues that contribute. NtpK, which is a V-ATPase rotor ring component, coordinates Na + with the essential carboxyl group of E139, the carbonyl group of Q65 and Q110, the hydroxyl group of T64 and the main chain carbonyl group of L61 (Murata et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Na + -driven V-type ATPase of Enterococcus hirae, the transmembrane complex V o , which conducts Na + (or Li + ), is composed of a membrane rotor ring (K-ring) comprising oligomers of NtpK and a single copy of the NtpI subunit. It has been suggested that the cavity size of the K-ring binding pocket contributes to the ion specificity, that five residues (L 61 , T 64 , Q 65 , Q 110 , E 139 ) of NtpK are involved in the Na + binding to the K-ring, and that the essential glutamate E 139 is conserved in the homologous subunits of H + -driven VATPase (Murata et al, 2005(Murata et al, , 2008. Bacterial flagellar motors are rotary motors which convert the electrochemical potential difference of a coupling ion (H + or Na + ) across the cytoplasmic membrane into torque, which rotates the flagellum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This subunit forms an oligomer, building up a ring structure of six or more copies which transports protons across the membrane. Recently, the structure of the ring from a bacterial V-ATPase has been described at 2.1 Å resolution and showed that 10 copies form the c ring [4]. This increasing molecular understanding in combination with the very promising biological profile of the archazolids renders these macrolide antibiotics attractive structures for further development.…”
mentioning
confidence: 99%
“…E. hirae V-ATPase requires all of its nine subunits (NtpFIKECGABD) (15) for its activity (5). The NtpK subunit forms the rotor ring of the V o moiety, which is responsible for ion translocation (17), and the Glu139 residue of NtpK, which constitutes the ion binding site (18), is crucial for its catalytic mechanism (21). Notably, E. hirae V-ATPase recognizes Na ϩ and Li ϩ with nearly equal affinities.…”
mentioning
confidence: 99%